Converting to Online Course and Program Delivery: The University of South Australia Case Study - Bruce King (Athabasca University Press, 2001)
The University of South Australia's (UniSA) approach to converting its distance education programs to online delivery is to manage it as a part of establishing an online teaching and learning environment for all of its programs. UniSA's move to online teaching and learning derives from a clear vision of its future, is informed and directed by a comprehensive framework for teaching and learning, and enabled by appropriate structures, processes and resources. The institution has chosen to develop a relatively low-cost, easy to use online teaching and learning environment that has facilitated large-scale conversion to the online mode for all teaching and learning, including traditional distance education.